Summary Record of Fifth Development Commissioners' Conference on Community Projects Held at Nainital - Ministry of Community Development Government of India (Ministry of Community Development Government of India, 1956)
The Fifth Development Commissioners’ Conference on Community Projects held at Nainital in May 1956, together with subsequent policy documents and administrative reports, represents a formative phase in shaping India’s integrated rural development framework during the Second Five-Year Plan. The deliberations underscored community development as a transformative movement aimed at addressing rural poverty through a balanced integration of agricultural advancement, small-scale and cottage industries, health, education, housing, and institutional capacity building. Emphasis was placed on increasing agricultural productivity through improved seeds, irrigation, cooperative farming, and effective water utilization, alongside the promotion of village and small-scale industries as vital sources of rural employment and income diversification. The conference and related initiatives highlighted the necessity of strong community participation through Panchayati Raj institutions, cooperative societies, and local leadership to ensure sustainability and ownership of development programs. Administrative coordination across departments, financial prudence, and systematic evaluation were identified as critical to overcoming implementation challenges. Considerable focus was also given to training and human resource development, including structured programs for Gram Sevaks, Block Development Officers, teachers, artisans, and higher administrative officials, supported by proposals for specialized institutions and apprenticeship schemes. Furthermore, the recommendations addressed essential social sectors such as rural health services, housing, women and youth welfare, and social education, advocating integrated planning at the block and village levels. The collective vision emerging from these documents reflects a comprehensive, people-centered approach to rural development, emphasizing self-reliance, decentralized governance, and sustained institutional support as the foundation for long-term socio-economic transformation in rural India.
Issued by Ministry of Community Development Government of India
Keywords: Community Development Projects; Rural Development Strategy; National Extension Service; Agricultural Productivity; Cottage and Small-Scale Industries; Cooperative Credit Systems; Panchayati Raj Institutions; Capacity Building and Training; Integrated Rural Planning; Community Participation; Administrative Coordination; Sustainable Development